2021
DOI: 10.1111/os.12996
|View full text |Cite
|
Sign up to set email alerts
|

Destination Joint Spacers: A Similar Infection‐Relief Rate But Higher Complication Rate Compared with Two‐Stage Revision

Abstract: Objective To evaluated the clinical outcomes of periprosthetic joint infection (PJI) patients with destination joint spacer compared with that of two‐stage revision. Methods From January 2006 to December 2017, data of PJI patients who underwent implantation with antibiotic‐impregnated cement spacers in our center due to chronic PJI were collected retrospectively. The diagnosis of PJI was based on the American Society for Musculoskeletal Infection (MSIS) criteria for PJI. One of the following must be met for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Thirteen studies reported the results of treatments in which a standardized prefabricated spacer was used [ 9 , 11 , 18 , 19 , 23 32 ], 5 studies reported on spacers that were intraoperatively produced by means of standardized molds or based on the method of Ivarson et al [ 33 ] (by separately duplicating the shape of the retrieved femoral head and the femoral stem component with bone cement) [ 17 , 31 , 34 36 ], 20 studies reported on intraoperatively manually shaped spacers [ 2 , 10 , 14 , 16 , 33 , 37 51 ], and two studies presented series in which different types of spacers were used. [ 7 , 15 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported the results of treatments in which a standardized prefabricated spacer was used [ 9 , 11 , 18 , 19 , 23 32 ], 5 studies reported on spacers that were intraoperatively produced by means of standardized molds or based on the method of Ivarson et al [ 33 ] (by separately duplicating the shape of the retrieved femoral head and the femoral stem component with bone cement) [ 17 , 31 , 34 36 ], 20 studies reported on intraoperatively manually shaped spacers [ 2 , 10 , 14 , 16 , 33 , 37 51 ], and two studies presented series in which different types of spacers were used. [ 7 , 15 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Metal-on-polyethylene articulating spacers are associated with a lower rate of complications and the absence of spacer fractures (43,44). It is not always possible to have a second stage because of economic and health reasons, and some patients may refuse reimplantation (45). Cai et al suggest using the spacer as a definitive treatment for PJI.…”
Section: Discussionmentioning
confidence: 99%
“…15 In the second stage of surgery, another opportunity occurs at the point of the reimplantation procedure to ensure contamination is eradicated by intraoperative coreview; histopathology submitted, including frozen sections, sample selection, and spacer removal; and finally, implantation of a new prosthesis because neither procedure was associated with persistent infection. 13,16,17 TSE is the ideal method in determining signs of chronic infection, sinus tract involvement, loose prostheses and other cases of multi-drug resistant infection where antimicrobial options are minimal. TSE is provided also for cases of PJI fungus.…”
Section: Discussionmentioning
confidence: 99%